MANAJEMEN STRES DENGAN LATIHAN BERPIKIR POSITIF DI MASA PANDEMI COVID-19 - Exda Hanung Lidiana; Norman Wijaya Gati; Fida' Husain (P3M Universitas Aisyiyah Surakarta, 2021)
The Covid-19 pandemic affects many aspects of people's lives, both in health, socially and economically where it can cause stress. Positive thinking training through health education is one way to reduce stress. Positive Thinking Therapy is a source of strength and a source of freedom. It is called a source of strength because it helps someone think of a solution until they get it. That way a person becomes more proficient, trusting, and stronger. It is called the source of freedom because with it a person will be free from suffering and confinement of negative thoughts and their effects on the physical. Stress was measured using the Hamilton Rating Scale for Anxiety (HARS). The method of activities carried out is the health education method, efforts to overcome stress with positive thinking exercises during the Covid-19 pandemic in Palur Wetan, Rt 01/05, Palur, Mojolaban, Sukoharjo, and was carried out for 1 month in November 2020. Results of the evaluation after counseling is carried out, namely most participants understand the problems or disturbances experienced and how the exercises can be carried out. There was a change and an increase in the participants' knowledge from not knowing to knowing.